Effect of Traits of the Trainers on Their Job Satisfaction and Job Performance in Krishi Vigyan Kendras in Rajasthan - Meena, B.S.; Singh, Baldeo (Indian Journal of Extension Education, 2009)
The present investigation aimed at analyzing the vocational trainings imparted by Krishi Vigyanb Kendras run by ICAR SAUs and NGOs in Rajasthan state and ascertain their comparative performance. The findings of this study reveals that maximum number of trainer of NGO KVK (70%) has post graduate degree whereas SAU and ICAR KVK had 42.10 and 27.27 post graduate trainers, respectively. The majority of trainers (57.90%) in SAU KVK were from rural agricultural families while about 60% in NGO KVKbelonged to urban areas. In terms of job satisfaction, the majority of the trainers in ICAR KVK (63.63%), SAU KVK (68.92%) and NGOKVK (50%) were reported to have medium level of job satisfaction. However, the trainers in SAU and ICAR KVK were relatively more satisfied than the trainer of NGO KVK. The job insecurity was the major contrainst for low level of job satisfaction. The trainers of NGO KVK stood first (40%) followed by ICAR and SAU in terms of job performance.